AIM’s accountability in financial sustainability: the role of market orientation - Adewale, Abideen Adeyemi (International Association of Computer Science and Information Technology (I A C S I T), 2014)
The paper aims at providing insights into how three dimensions of market orientation namely; customer orientation, competitor orientation and inter-function coordination affect the financial performance of Amanah Ikhtiar Malaysia (AIM) as the oldest microfinance institution in South East Asia. Using a cross sectional survey, Partial Least Squares (PLS) as a variance-based structural equation modeling (SEM), the current study examines the AIM’s accountability on market orientation in financial sustainability. The results provided empirical evidences that indicate customer orientation and inter-function coordination significantly affect financial performance of AIM. Nevertheless, competitor orientation has a negative and insignificant effect on sustainable financial performance of AIM. The result of the paper enhanced further the literature in understanding the long-term sustainable financial performance-based market orientation.